Pengaruh Perbedaan Waktu Setting terhadap Hasil Tangkapan Ikan Tuna Albakore (Thunnus alangunga) pada Alat Tangkap Longline di Perairan Seas Samudra Pelabuhan Benoa - Nizar Nurkalam; M Tajuddin Noor; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Tuna fisheries are a strategic sector in Indonesia's fishing industry, contributing significantly to the national economy. Albacore tuna (Thunnus alalunga) has high economic value and is one of the main commodities in international trade. This study aims to analyze the effect of different longline setting times on albacore tuna catches in the Seas of Benoa Harbor. The setting times compared were morning (08:00–10:00) and afternoon (14:00–16:00), focusing on the quantity and weight of the catch. The research method used was an experimental approach with two setting time treatments and nine replications for each treatment. Data obtained were analyzed using a T-test to determine significant differences between morning and afternoon catches. The results showed that the average catch in the morning was higher than in the afternoon, both in terms of individual count and fish weight. The average fish weight obtained in the morning was 63.78 kg, while in the afternoon, it was only 28.67 kg. Statistical analysis indicated a significant difference between morning and afternoon catches, with a T-Statistic value of 2.38, which exceeded the T-Critical value (2.12) at a 5% significance level (p-value = 0.0366). This suggests that the morning setting time is more optimal for catching albacore tuna than the afternoon setting. Catch variation was also greater in the morning, as indicated by a higher standard deviation compared to the afternoon. This difference may be attributed to the daily migration patterns of albacore tuna, which are more active in feeding during the morning, as well as environmental factors such as water temperature and light intensity. Based on these findings, this study recommends that fishers in the Seas of Benoa Harbor should set their longline fishing gear in the morning to maximize their catch.